2015
DOI: 10.1681/asn.2015040433
|View full text |Cite
|
Sign up to set email alerts
|

C4d Staining in the Diagnosis of C3 Glomerulopathy

Abstract: ally regulates an early-response gene containing homology to platelet proteins. Nature 315: 672-676, 1985 15. Farber JM: A macrophage mRNA selectively induced by gammainterferon encodes a member of the platelet factor 4 family of cytokines. Proc Natl Acad Sci U S A 87: 5238-5242, 1990 16. Kawai T, Takeuchi O, Fujita T, Inoue J, Mühlradt PF, Sato S, Hoshino K, Akira S: Lipopolysaccharide stimulates the MyD88-independent pathway and results in activation of IFN-regulatory factor 3 and the expression of a subset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…Additionally, it is a potential diagnostic tool for C3 glomerulonephritis or TMA. 25,26 In the present study with more than 1000 patients, we confirmed that glomerular C4d staining can also be used as a stable biomarker for disease progression in J o u r n a l P r e -p r o o f IgAN. However, before it is used in clinical practice, a number of issues need to be resolved.…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, it is a potential diagnostic tool for C3 glomerulonephritis or TMA. 25,26 In the present study with more than 1000 patients, we confirmed that glomerular C4d staining can also be used as a stable biomarker for disease progression in J o u r n a l P r e -p r o o f IgAN. However, before it is used in clinical practice, a number of issues need to be resolved.…”
Section: Discussionsupporting
confidence: 79%
“…Activation of complement in the classical pathway with cleavage of C4 and subsequent binding of the C4d fraction covalently to the site of activation is commonly observed in the antibody-mediated rejection pathway posttransplantation. Also, Sethi and colleagues 10 and Cook 11 proposed the use of C4d immunohistochemical staining to differentiate PIGN and C3 glomerulopathy, where C4d would be absent in C3 glomerulopathy. Immunohistochemistry for C4d was negative in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that staining for C4d can distinguish C3G from immune complex-mediated GN, though its role is not established. [5][6][7] Further studies on both frozen and paraffin sections are required.…”
Section: C3gmentioning
confidence: 99%